Absorbable bone hemostasis repair stent as well as preparation method and application thereof

By preparing a bone hemostasis and repair scaffold coated with PLGA/zinc stearate/potassium bromide and encapsulating calcium phosphate particles, the shortcomings of existing materials in hemostasis and bone repair promotion in orthopedic trauma treatment are overcome, achieving the effects of strong hemostasis, anti-ulceration and inflammation regulation, and promoting bone repair.

CN121338097AActive Publication Date: 2026-01-16BEOGENE BIOTECH GUANGZHOU

Patent Information

Application Number
CN202511912827.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-01-16
Estimated Expiration
2045-12-18

AI Technical Summary

Technical Problem

There is a lack of materials in current orthopedic trauma treatment that simultaneously possess good bone hemostasis and promote bone repair, and existing materials are insufficient in terms of anti-fracture ability and inflammation regulation function.

Method used

An absorbable bone hemostatic repair scaffold is used, consisting of calcium phosphate particles coated with PLGA/zinc stearate/potassium bromide. Through synergistic action, it regulates the inflammatory response and promotes bone repair. The preparation steps include: mixing polylactic acid-glycolic acid copolymer, zinc stearate, potassium bromide and calcium phosphate particles to form a malleable bone hemostatic repair scaffold.

Benefits of technology

It achieves strong hemostasis, anti-ulceration, and bone repair promotion, and effectively regulates the inflammatory response during the inflammatory period to ensure the quality and efficiency of bone repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121338097A_ABST
    Figure CN121338097A_ABST
Patent Text Reader

Abstract

The invention relates to an absorbable bone hemostasis and repair stent. The absorbable bone hemostasis and repair stent comprises the following raw materials in parts by weight: 15-60 parts of an excipient, 15-60 parts of a softening agent and 5-70 parts of a bone repair promoting component, the excipient is prepared from a polyoxyethylene-polyoxypropylene copolymer; the softening agent comprises a semi-solid mobile phase polymer; the bone repair promoting component comprises a coating and a core, the coating comprises a polylactic acid-glycolic acid copolymer, zinc stearate and potassium bromide, the core comprises calcium phosphate particles, and the coating wraps the surface of the core. The preparation method comprises the following steps: preparing the bone repair promoting component; and preparing the absorbable bone hemostasis repair stent. The absorbable bone hemostasis and repair stent is high in hemostasis and collapse resistance and has good inflammation regulation and bone repair promoting effects. The absorbable bone hemostasis and repair stent can be used for bone hemostasis and bone repair promotion of any bone injury wound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of bone hemostasis and repair materials, and in particular to an absorbable bone hemostasis and repair scaffold, its preparation method, and its application. Background Technology

[0002] Clinically, the treatment of orthopedic trauma inevitably faces two issues: bone bleeding and post-traumatic bone repair. Therefore, clinical orthopedic trauma treatment always utilizes medical products that aim to stop bleeding and promote bone healing. Currently, there are standalone medical products that address both bleeding and bone repair, but no product solution simultaneously provides effective hemostasis and promotes bone repair. Bone injury progresses through the following stages: bleeding from the bone wound → inflammation → proliferative remodeling.

[0003] Bone injury bleeding mainly occurs in cancellous bone. Cancellous bone does not have obvious arterial / venous trunks, but is composed of a network of sinusoidal capillaries (blood sinuses) with a diameter of 20~100μm. These blood sinuses have thin walls (only 1~2 layers of endothelial cells, no smooth muscle layer) and poor elasticity. After injury, they cannot close themselves through "vasoconstriction". Usually, hemostasis can only be achieved by physical sealing with bone wax.

[0004] The inflammatory phase of bone injury is the first core stage of the bone repair process, typically lasting 0-7 days after injury (the exact duration varies depending on the severity of the injury and individual immune status). This inflammatory phase is not a single "inflammatory state," but rather a progressive process of "pro-inflammatory → anti-inflammatory → repair initiation" over time, laying the foundation for the subsequent proliferative repair and bone remodeling phases. Abnormalities in the inflammatory phase of bone injury can severely impact the subsequent bone repair process. Therefore, good bone hemostatic and repair materials should be able to regulate inflammation, achieving "inhibition of excessive inflammation, promotion of the transformation of inflammation into repair, and adaptation to the bone healing sequence," avoiding post-hemostasis repair obstacles (such as nonunion or bone infection) due to inflammatory disturbances.

[0005] The bone proliferation and remodeling phase is a crucial functional stage in bone injury repair, succeeding the inflammatory phase and encompassing two major processes: the "proliferative repair phase (2-8 weeks post-injury)" and the "bone remodeling phase (8 weeks to 2 years post-injury)." The bone proliferation and remodeling phase is the longest and most complex stage in bone injury repair, with challenges concentrated in three dimensions: "osteogenesis-osteogenesis balance regulation," "repair-functional adaptation," and "microenvironmental interference factors." These challenges directly affect the efficiency and quality of bone repair, potentially leading to delayed healing, nonunion, or poor recovery of mechanical function. Therefore, materials used for bone hemostasis and repair after bone injury are extremely important.

[0006] Existing technologies have disclosed materials that simultaneously possess bone hemostasis and bone repair functions, such as bone wax with bone repair function, its preparation method, and its application. The components include polyoxypropylene-polyoxyethylene copolymer, strontium-doped carbon-containing nano-hydroxyapatite, etc., simultaneously possessing bone hemostasis and bone repair functions. However, this method has poor anti-collapse ability and lacks zinc ions, thus exhibiting no significant inflammatory regulatory function. A plastic bone graft composition has also been disclosed, containing approximately 10-50% by weight of biphasic calcium phosphate particles containing hydroxyapatite and tricalcium phosphate; and approximately 1-40% by weight of at least one bioactive glass. However, this method primarily uses water-soluble polymers, resulting in a highly plastic material with poor anti-collapse ability and no significant inflammatory regulatory function. Furthermore, bone hemostasis and repair materials and their preparation methods have been disclosed, with the raw materials comprising 4-80 parts by weight of bioactive glass and 1-50 parts by weight of excipients. However, this method lacks significant inflammatory regulatory effects. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides an absorbable bone hemostatic repair scaffold, characterized in that the absorbable bone hemostatic repair scaffold comprises the following raw materials in parts by weight: 15-60 parts of excipient, 15-60 parts of softener, and 5-70 parts of bone repair promoting components; the excipient comprises polyoxyethylene-polyoxypropylene copolymer (PEG-ran-PPG); the softener comprises a semi-solid mobile phase polymer; The bone-repairing component includes a coating and a core. The coating includes polylactic acid-glycolic acid copolymer, zinc stearate, and potassium bromide. The core includes calcium phosphate salt particles. The coating is wrapped around the surface of the core.

[0008] In one embodiment, the excipient includes at least one of poloxamer P188, poloxamer 407, poloxamer P338, and poloxamer F108.

[0009] In one embodiment, the softener includes at least one of vitamin E acetate and polyoxyethylene-polyoxypropylene random copolymer; The calcium phosphate particles include α-tricalcium phosphate, β-tricalcium phosphate, or hydroxyapatite.

[0010] In one embodiment, the potassium bromide particles have a diameter ≤100 nm, and the calcium phosphate particles have a size of 1~200 μm.

[0011] A second aspect of the present invention also provides a method for preparing the above-mentioned absorbable bone hemostatic repair scaffold, comprising the following steps: Preparation of bone-repairing components: Mix polylactic acid-glycolic acid copolymer, zinc stearate, potassium bromide and calcium phosphate salt particles, place in an environment of 135℃~175℃, stir and mix evenly, transfer to room temperature, continue stirring, and cool down to obtain the final product; Preparation of absorbable bone hemostatic repair scaffold: Mix excipients, softeners and bone-repairing components, keep heating, stir and mix evenly, shape, and cool to obtain the scaffold.

[0012] In one embodiment, in the preparation of the bone-repairing component, the mass ratio of the polylactic acid-glycolic acid copolymer: the zinc stearate: the potassium bromide: the calcium phosphate particles is (0.3~0.6):(0.1~0.3):(0.03~0.06):1; In the polylactic acid-glycolic acid copolymer (PLGA), the molar ratio of lactic acid (LA) monomer to glycolic acid (GA) monomer is 75:25.

[0013] In one embodiment, in the preparation of the bone-repairing component, the stirring speed for uniform mixing is 30-60 r / min, and the stirring time is ≥30 min; the stirring speed for continued mixing is 30-50 r / min.

[0014] In one embodiment, during the preparation of the absorbable bone hemostatic repair stent, the heating temperature is maintained at 60~90℃ for ≥1h, the stirring speed for uniform mixing is 30~60r / min, and the stirring time is ≥30min.

[0015] The third aspect of the present invention also provides the application of the above-mentioned absorbable bone hemostasis and repair scaffold, or the absorbable bone hemostasis and repair scaffold obtained by the above preparation method, in the preparation of bone hemostasis and repair products.

[0016] In addition, the present invention also provides a bone hemostasis and repair product, which includes the above-mentioned absorbable bone hemostasis and repair scaffold, or the absorbable bone hemostasis and repair scaffold obtained by the above preparation method.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a bone hemostatic and repair scaffold with strong hemostatic and anti-collapse capabilities, excellent bone hemostasis, and good anti-inflammatory and bone repair effects. During the early inflammatory stage of bone repair, the outer PLGA / zinc stearate / potassium bromide coating degrades and releases Zn. 2+ (Zinc ions) and Br - Bromine ions can synergistically regulate inflammatory responses and activate repair cell functions, laying a crucial foundation for subsequent bone tissue regeneration. Combined with a phosphate nucleus, they can effectively accelerate the bone repair process and ensure the quality of bone repair. Attached Figure Description

[0018] Figure 1 Electron micrograph of calcium phosphate particles coated with PLGA / zinc stearate / potassium bromide; Figure 2Figure showing the results of slow-release zinc and bromide ions from calcium phosphate particles coated with PLGA / zinc stearate / potassium bromide. Figure 3 A physical illustration of the plasticity of a bone hemostatic repair scaffold; Figure 4 Image of skull repair capability of bone hemostasis repair scaffold (Micro CT 3D, scale bar 1mm). Detailed Implementation

[0019] This invention first prepares calcium phosphate particles (1μm~200μm) coated with PLGA / zinc stearate / potassium bromide using a hot-melt coating method. Then, these particles are hot-melt blended with an excipient (polyoxyethylene-polyoxypropylene copolymer) and a softener, followed by cooling and shaping to obtain an absorbable and arbitrarily shaped bone hemostatic repair scaffold. Thanks to the softening ability and semi-hydrophobic properties of the softener, this bone hemostatic repair scaffold exhibits good hemostasis and anti-collapse properties. During bone repair, the excipient and softener gradually degrade and are absorbed, exposing the PLGA / zinc stearate / potassium bromide coated calcium phosphate particles to the bone wound environment. Zinc stearate typically has difficulty releasing Zn. 2+ However, the acidic substances (lactic acid, glycolic acid) produced by PLGA degradation will promote the degradation of zinc stearate into stearic acid and Zn. 2+ The degradation of PLGA and zinc stearate will lead to the presence of Br in the coating. - The release of PLGA and zinc stearate in the coating. Therefore, the synergistic degradation of PLGA and zinc stearate in the coating affects the release of Zn. 2+ and Br - The sustained release plays a crucial role. In the early inflammatory stage of bone repair, the Zn released during the degradation of the outer PLGA / zinc stearate / potassium bromide coating... 2+ (Zinc ions) and Br - Bromine ions can synergistically regulate inflammatory responses and activate repair cell functions, laying a crucial foundation for subsequent bone tissue regeneration. They can effectively accelerate the bone repair process and ensure its quality. When the outer PLGA / zinc stearate / potassium bromide coating degrades and the core calcium phosphate particles are exposed and come into contact with the bone wound, its role shifts from "assisting in inflammation regulation" to "promoting bone regeneration and structural reconstruction"—by providing an "inorganic scaffold" for bone regeneration, releasing phosphate / calcium ions to regulate the microenvironment and guide orderly bone tissue remodeling.

[0020] The bone hemostasis and repair scaffold of this invention is a malleable bone hemostasis and repair scaffold that can be widely used for filling bone defects. It has strong anti-collapse ability, can stop bleeding immediately, regulate inflammation, and promote bone repair.

[0021] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0023] Unless otherwise specified, all reagents, materials, and equipment used in this embodiment are commercially available; unless otherwise specified, all test methods are conventional test methods in this field.

[0024] Example This invention provides a method for preparing an absorbable bone hemostatic repair scaffold, wherein the LA:GA molar ratio of PLGA used is 75:25 (75% lactic acid-25% glycolic acid copolymer), with a melting point of 110℃~130℃ and a thermal decomposition temperature of 180℃~190℃; the zinc stearate used has a melting point of 118℃~125℃ and a thermal decomposition temperature of 200℃~230℃; the potassium bromide used has a particle size not exceeding 180,000 mesh (not exceeding 100nm); and the calcium phosphate salt used has a particle size of 1μm~200μm. The preparation method specifically includes the following steps: (1) Preparation of calcium phosphate particles coated with PLGA (polylactic acid-glycolic acid copolymer) / zinc stearate / potassium bromide coating PLGA, zinc stearate, potassium bromide, and calcium phosphate particles were mixed in a mass ratio of 0.5:0.2:0.05:1. The mixture was then placed in a high-temperature environment of 135℃~175℃. After the PLGA and zinc stearate were completely melted, the PLGA, zinc stearate, potassium bromide, and calcium phosphate particles were thoroughly stirred and mixed at a speed of 30r / min~60r / min for at least 30min. The mixture was then transferred to room temperature and stirred continuously at a speed of 40r / min±10r / min. Excessive stirring speed will damage the coating, while insufficient speed will cause the particles to clump together. Once the material temperature has cooled to room temperature, a PLGA / zinc stearate / potassium bromide coating will be formed on the surface of the calcium phosphate particles, resulting in calcium phosphate particles coated with this PLGA / zinc stearate / potassium bromide coating.

[0025] (2) Preparation of absorbable bone hemostatic repair scaffold The absorbable bone hemostatic repair scaffold is composed of 15-60 parts of excipients, 15-60 parts of softener, and 5-70 parts of bone-repairing components. The excipients include any one or a combination of two of poloxamer P188, poloxamer 407, poloxamer P338, and poloxamer F108. The softener is a semi-solid mobile phase polymer, including any one or a combination of two of vitamin E acetate and polyoxyethylene-polyoxypropylene random copolymer (PEG-ran-PPG). The bone-repairing component is calcium phosphate particles coated with a PLGA / zinc stearate / potassium bromide coating prepared in step (1).

[0026] According to the specified ratio, mix the excipients, softeners, and bone-repairing ingredients in a clean container. Maintain heating at 60-90℃ for at least 1 hour to fully soften the excipients and softeners. Then, stir at 30-60 rpm for at least 30 minutes to ensure the excipients, softeners, and bone-repairing ingredients are evenly mixed. Pour the mixture into a stainless steel mold and allow it to cool and solidify at room temperature. Demolding yields the finished product.

[0027] The specific formulations of the embodiments and comparative examples of the present invention are shown in Table 1. After heating, softening, mixing and cooling to form according to the above preparation method, an absorbable bone hemostatic repair scaffold can be obtained.

[0028] Table 1

[0029] Implementation effect evaluation 1. Take samples from Examples 1-6 and Comparative Examples 1-8 and evaluate their plasticity (softening), anti-collapse properties, in vitro hemostatic effect (in vitro occlusion ability), in vitro osteogenic ability, and anti-inflammatory ability.

[0030] Examples 1-6 verified the feasibility of the formulation. Comparative Examples 1 and 2 verified the ratio range of the bone-repairing components; Comparative Examples 3 and 4 verified the ratio range of the softener and excipients; and Comparative Examples 5-8, compared with Example 1, verified the slow-release Zn2+ coated with PLGA / zinc stearate / potassium bromide onto calcium phosphate particles. 2+ and Br - It has a synergistic effect in promoting anti-inflammation and bone repair.

[0031] The specific evaluation methods and standards are as follows: 1. Plasticity: The bone hemostasis repair stent should have good plasticity when squeezed by hand. The material should not be too hard or too soft.

[0032] 2. Anti-collapse property: Simulating the in vivo body fluid environment, the structural changes of the material under constant temperature and static immersion were observed, and its morphological stability was analyzed. Materials from each group were prepared into uniformly sized samples (cylinders with a diameter of 1 cm and a thickness of 5 mm), immersed in PBS at pH 7.4, and allowed to stand at 37°C. The time for complete material collapse should be no less than 8 hours to minimize the risk of secondary bleeding from the bone wound.

[0033] 3. Extracorporeal hemostasis effect (extracorporeal sealing capability): Prepare a hollow plastic tube with a diameter of 5mm and a length of 1.91m (equivalent to a pressure of 140mmHg, which is equal to the maximum arterial bleeding pressure in the human body). Seal one end with the softened and shaped material, and add purified water from the other end to simulate the sealing effect of the maximum pressure of intramedullary hemorrhage in the human body. The sealing time should be no less than 60 minutes, that is, no water should leak from the sealing site within 60 minutes.

[0034] 4. Osteogenesis capacity: Osteoblast viability is an important indicator for evaluating bone healing capacity. Osteoblasts and materials were co-inoculated into the culture medium and cultured for 72 hours. Compared with the blank control (ordinary culture medium), the viability of osteoblasts in the experimental group should be no less than 1.2 times.

[0035] 5. Anti-inflammatory capacity: One important indicator of anti-inflammatory activity is the ability to promote the transformation of macrophages from the pro-inflammatory phenotype M1 to the anti-inflammatory phenotype M2. Mouse macrophage RAW264.7 was selected as the research subject. After co-culturing the cells with equal amounts of materials from each group for 48 hours, the CD86 levels in each group were detected by flow cytometry. + Cells (M1 phenotype), CD206 + For cells (M2 phenotype), calculate the M2 / M1 ratio; M2 / M1 should be greater than 1.5.

[0036] II. Verify the experimental results.

[0037] 1. Morphological observation of calcium phosphate particles coated with PLGA / zinc stearate / potassium bromide coating The structure of the calcium phosphate particles coated with the prepared PLGA / zinc stearate / potassium bromide coating was observed by scanning electron microscopy.

[0038] The results are as follows Figure 1 As shown, the calcium phosphate particles coated with PLGA / zinc stearate / potassium bromide still exhibit an independent granular structure.

[0039] 2. Results of slow-release of zinc and bromide ions from calcium phosphate particles coated with PLGA / zinc stearate / potassium bromide The prepared PLGA / zinc stearate / potassium bromide coated calcium phosphate particles were dispersed in PBS solution at pH 7.4, and Zn content was measured at 1, 2, 4, 6, 8, 10, 12, and 14 days. 2+and Br - The sustained-release ratio.

[0040] Zn 2+ and Br - The sustained-release ratio results are as follows Figure 2 As shown, the release rate reached about 50% on day 6 and the sustained release rate exceeded 70% on day 10, indicating that the degradation process of the PLGA / zinc stearate / potassium bromide coating can basically match the process of bone wound inflammation, anti-inflammation to repair, and has a positive promoting effect on bone repair.

[0041] Zinc stearate is generally difficult to release Zn. 2+ However, the acidic substances (lactic acid, glycolic acid) produced by PLGA degradation will promote the degradation of zinc stearate into stearic acid and Zn. 2+ The degradation of PLGA and zinc stearate will lead to the presence of Br in the coating. - The release of PLGA and zinc stearate in the coating. Therefore, the synergistic degradation of PLGA and zinc stearate in the coating affects the release of Zn. 2+ and Br - The sustained release plays a key role.

[0042] 3. Plasticity of bone hemostasis and repair scaffolds The prepared bone hemostatic repair scaffold has good plasticity and can be molded into various shapes, such as Figure 3 As shown, Example 1 can be molded into spherical or cylindrical shapes, and can be used clinically to fill, stop bleeding, and repair bone defects of various shapes.

[0043] 4. Skull repair capability of bone hemostasis and repair scaffold Bama miniature pigs were selected as experimental animals because their skull anatomy is similar to that of humans, exhibiting a distinct diploic structure resembling that of an adult human skull. A model of a critical bone defect (25 mm in diameter × 10 mm in depth) was created in the pig's skull using a high-speed cranial drill. Hemostasis at the defect site was then achieved using the bone hemostasis and repair scaffolds from Comparative Example 5 and Example 1, respectively. Micro-CT 3D reconstruction of the skull defect was performed at week 8, and the results are as follows: Figure 4 As shown.

[0044] The bone repair effect in the experimental group (Example 1) was significantly better than that in the control group (Comparative Example 5). This demonstrates that the prepared PLGA / zinc stearate / potassium bromide coating encapsulates calcium phosphate particles for sustained-release Zn. 2+ and Br - Synergistic promotion of bone repair.

[0045] The results of comparing the effects of the examples and the comparative examples are shown in Table 2.

[0046] Table 2 Comparison of effects between the examples and the comparative examples

[0047] Comparison results: 1. According to Comparative Examples 1 and 2, the bone-repairing components affect the effectiveness, plasticity, anti-collapse properties, and occlusion effect of the bone hemostasis and repair scaffold. If the proportion of bone-repairing components is too low, the in vitro bone-repairing ability will be unqualified; if the proportion of bone-repairing components is too high, since the bone-repairing components are in powder form, the material will be too soft and the anti-collapse properties will not meet the requirements, which will lead to the material being washed away by water during in vitro occlusion and hemostasis, resulting in occlusion failure.

[0048] 2. According to Comparative Examples 3 and 4, excipients and softeners affect the plasticity (material texture) and in vitro hemostasis effect of the material. If the proportion of softener is too low and the proportion of excipient is too high, the material texture will be too hard and difficult to shape; if the proportion of softener is too high and the proportion of excipient is too low, the material texture will be too soft. When simulating in vitro hemostasis, the material texture is too soft and is easily washed away by water pressure, resulting in occlusion failure.

[0049] 3. Based on Example 1 and Comparative Example 5, and the experimental results Figure 4 This demonstrates that the prepared PLGA / zinc stearate / potassium bromide coating encapsulates calcium phosphate particles for sustained-release Zn. 2+ and Br - It has a positive promoting effect on bone repair. The formulations of Example 1 and Comparative Example 5 are basically the same, the only difference being that the bone repair promoting component in Example 1 is calcium phosphate salt particles coated with PLGA / zinc stearate / potassium bromide, while Comparative Example 5 is calcium phosphate salt particles without zinc bromide ion coating.

[0050] 4. Comparison of Examples 5-8 with those of Examples 1-2 demonstrates that the prepared PLGA / zinc stearate / potassium bromide coating encapsulates calcium phosphate particles for sustained-release Zn. 2+ and Br - It possesses synergistic anti-inflammatory and repair-promoting abilities, both of which are indispensable. Replacing bromide ions in the coating with magnesium ions significantly reduces the synergistic effect.

[0051] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0052] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. An absorbable bone hemostatic repair scaffold, characterized in that, The absorbable bone hemostasis repair bracket comprises the following raw materials in parts by weight: excipient 15-60 parts, softening agent 15-60 parts, and bone repair promoting component 5-70 parts; the excipient comprises polyoxyethylene-polyoxypropylene copolymer; and the softening agent comprises semi-solid flow phase polymer. The bone repair promoting component comprises a coating and a core, the coating comprises polylactic acid-glycolic acid copolymer, zinc stearate, and potassium bromide, and the core comprises calcium phosphate salt particles, and the coating is wrapped on the surface of the core.

2. The absorbable osteostoppage repair scaffold of claim 1, wherein, The excipient comprises at least one of poloxamer P188, poloxamer 407, poloxamer P338, and poloxamer F108.

3. The absorbable osteostoppage repair scaffold of claim 1, wherein, The softening agent comprises at least one of vitamin E acetate and polyoxyethylene-polyoxypropylene random copolymer. The calcium phosphate salt particles comprise α-tricalcium phosphate, β-tricalcium phosphate, or hydroxyapatite.

4. The absorbable osteostoppage repair scaffold of claim 1, wherein, The particle size of the potassium bromide is less than or equal to 100 nm, and the size of the calcium phosphate salt particles is 1-200 μm.

5. The method for preparing the absorbable bone hemostatic repair scaffold as described in any one of claims 1-4, characterized in that, The method comprises the following steps: Preparation of the bone repair promoting component: polylactic acid-glycolic acid copolymer, zinc stearate, potassium bromide, and calcium phosphate salt particles are mixed, stirred and uniformly mixed in an environment at 135-175 ℃, transferred to a room temperature environment, continuously stirred, and cooled to obtain the bone repair promoting component; Preparation of the absorbable bone hemostasis repair bracket: the excipient, the softening agent, and the bone repair promoting component are mixed, heated, stirred and uniformly mixed, shaped, and cooled to obtain the absorbable bone hemostasis repair bracket.

6. The production method according to claim 5, wherein In the preparation of the bone repair promoting component, the mass ratio of the polylactic acid-glycolic acid copolymer: the zinc stearate: the potassium bromide: the calcium phosphate salt particles is (0.3-0.6):(0.1-0.3):(0.03-0.06):

1. In the polylactic acid-glycolic acid copolymer, the molar ratio of lactic acid monomer to glycolic acid monomer is 75:

25.

7. The preparation method according to claim 5, characterized in that, In the preparation of the bone repair promoting component, the stirring speed for stirring and uniformly mixing is 30-60 r / min, and the stirring time is greater than or equal to 30 min; and the stirring speed for continuous stirring is 30-50 r / min.

8. The preparation method according to claim 5, characterized in that, In the preparation of the absorbable bone hemostasis repair bracket, the temperature for heating is 60-90 ℃, the heating time is greater than or equal to 1 h, the stirring speed for stirring and uniformly mixing is 30-60 r / min, and the stirring time is greater than or equal to 30 min.

9. Use of the absorbable bone hemostasis repair bracket according to claims 1-4 or prepared by the preparation method of claims 5-8 in the preparation of a bone hemostasis repair product.

10. A bone hemostatic repair product, characterized in that, The bone hemostasis repair product comprises the absorbable bone hemostasis repair bracket according to claims 1-4 or prepared by the preparation method of claims 5-8.

Citation Information

Patent Citations

  • Bone wax with bone repair function as well as preparation method and application thereof

    CN109432487A

  • Metal-phosphonic acid nanocluster drug-loaded hybrid coating capable of degrading metal surface bone immunoregulation and promoting osteogenesis as well as preparation method and application of metal-phosphonic acid nanocluster drug-loaded hybrid coating

    CN118873747A

  • Malleable implants including an oxysterol and methods of use

    US20160367728A1

  • Inorganic materials for hemostatic modulation and therapeutic wound healing

    WO2006110393A1

Cited By

  • Antibacterial self-curing absorbable bone repair material as well as preparation method and application thereof

    CN121731556A